Crossing Complex Boundaries: Transnational Trade Union Education - Walker, Steve; Creanor, Linda (Proceedings of the International Conference on Networked Learning, 2004)
Collaboration across boundaries in work and learning is a feature of networked organisation. We outline a framework for analysing learning events in terms of multiple boundaries of differing types, significance, role and severity. These boundaries may provide either/both obstacles to and opportunities for learning, particularly in a networked environment. Tutors and learners may negotiate these various boundaries with a variety of digital practices and artefacts. We apply this provisional framework of boundaries, artefacts and practices to the case of transnational trade union education, in which tutors and course participants negotiate a complex mix of boundaries.